2017
DOI: 10.1902/jop.2016.160355
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Sectional Evaluation of Periodontal Status and Microbiologic and Rheumatoid Parameters in a Large Cohort of Patients With Rheumatoid Arthritis

Abstract: Patients with RA had worse periodontal conditions than HC participants. Although a trend for higher F. nucleatum and P. gingivalis concentrations in aCCP-positive patients with RA was found, importance of periodontal pathogenic bacteria and rheumatoid parameters in the interrelationship between periodontitis and RA remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
57
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 51 publications
12
57
1
1
Order By: Relevance
“…However, no association between the overall HAQ scores with oral hygiene was found in this study. This is similar to other studies reporting on this connection (Bello-Gualtero et al 2015;Dissick et al 2010;Schmickler et al 2016).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, no association between the overall HAQ scores with oral hygiene was found in this study. This is similar to other studies reporting on this connection (Bello-Gualtero et al 2015;Dissick et al 2010;Schmickler et al 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Mercado et al (2001) found a relationship between the degree of functional debilitation due to RA and PD severity while Garib and Qaradaxi (2011 ) also reported a relationship between HAQ scores with plaque index, alveolar bone loss and clinical attachment loss of the periodontium. In contrast, Schmickler et al (2016) used self-reported limitations in motor skills reported in a self-administered questionnaire to assess function and found that limited motor skills had no influence on periodontal conditions (Schmickler et al 2016). This is in line with the HAQ scores from other reports (Bello-Gualtero et al 2015;Dissick et al 2010) that were not associated with measures of oral or periodontal disease.…”
Section: Introductionmentioning
confidence: 59%
“…A similar interrelationship as between PD and IBD has comprehensively been described for PD and rheumatoid arthritis in literature . Thereby, periodontal pathogenic bacteria, especially Porphyromonas gingivalis are controversially discussed to be a causative link between PD and rheumatoid arthritis . Furthermore, mechanisms of the innate immunity, especially release and activation of matrix metalloproteinase‐8 (MMP‐8), might be involved in this interrelationship .…”
Section: Introductionmentioning
confidence: 63%
“…11 Thereby, periodontal pathogenic bacteria, especially Porphyromonas gingivalis are controversially discussed to be a causative link between PD and rheumatoid arthritis. [12][13][14] Furthermore, mechanisms of the innate immunity, especially release and activation of matrix metalloproteinase-8 (MMP-8), might be involved in this interrelationship. 15 It appears questionable if similar pathways are involved in the association between IBD and PD.…”
mentioning
confidence: 99%
“…Data from NHANES 2009–2012 showed that age was associated with the prevalence of gingival disease, and that 46% of dental adults in the US aged ≥30 years had gingival disease [23]. Other studies were consistent with these data and showed that the prevalence of gingival disease in RA patients was significantly associated with age [16, 32, 33]. A study evaluating the prevalence and severity of gingival disease in 40 RA patients showed that the prevalence of gingival disease was higher in men, smokers, and older patients [34, 35].…”
Section: Discussionmentioning
confidence: 83%